Edsonina Martins Novais: história de vida e contribuição para educação combinadense - Vasconcelos, Raylla Maria Martins (Universidade Federal do Tocantins, 2024)
This work presents a portion of the life story of Edsonina Martins, relating it to the history of Combinado-TO, the city where she resides. Known as Sonina in the city, she is a retired teacher and is considered a pioneering educator of the city she lives in. Combinado-TO was founded by Mauro Borges in 1962 through a land reform plan inspired by the Israeli kibbutz model. The history of the city was shaped through the experiences of its residents, particularly after the project was terminated in 1964 due to the intervention of the military regime in the country. The aim of this research is to investigate the significance of the educator and the marks she left on the educational foundation of the Combinado-TO do Tocantins community, intertwined with her life story. The adopted methodology is autobiographical or life history, primarily in dialogue with the following authors: Maria Helena Menna Barreto Abrão (2003) as a methodological reference, Redenir dos Santos (2002) for community characterization, and Simon Lima Brito (2020) for the political and social aspects. However, the core foundation is built upon the accounts of Edsonina and some participants in her journey. This study is crucial for the community as it highlights the pioneer's contributions and documents a part of local history. Among the findings, we recognize the value of Edsonina for the community, the evidence of overcoming challenges faced by the population, and the importance of education. The structure of the work includes an introduction, a descriptive memoir of the author, a development section that explores the city's setting, the life story of the researcher, and the relationship between her and the participants, emphasizing the significance of memories. Finally, the concluding remarks bring closure to the work